The Influence of Leadership Style on Employee Performance at Bangkalan Community Health Center - Enggal Sari Maduratna; Eklamsia Sakti; Nailufar Firdaus (Journal for Quality in Public Health, 2026)
Employee performance is an important factor in supporting the quality of health services at Community Health Centers (Puskesmas). One organizational factor suspected of influencing employee performance is leadership style. This study aims to analyze the influence of various leadership styles on employee performance at the Bangkalan Community Health Center. This study used a quantitative approach with a cross-sectional design through a survey method. The study was conducted in April 2024 at the Bangkalan Community Health Center, Bangkalan Regency, with 80 employees selected using a purposive sampling technique. Data were collected using a Likert scale questionnaire and analyzed using multiple linear regression with the help of IBM SPSS software. The independent variables in this study include transformational, transactional, situational, democratic, authoritarian, laissez-faire, and digital leadership styles, while the dependent variable is employee performance. The results showed that partially the authoritarian leadership style had a p-value of 0.013 with a t-count of 2.559 on employee performance. Thus, the authoritarian leadership style has a significant positive effect on employee performance. Meanwhile, transformational, transactional, situational, democratic, laissez-faire, and digital leadership styles failed to answer the hypothesis. These findings indicate that, in the context of Community Health Centers (Puskesmas) as public health service organizations, a leadership style that emphasizes clear direction, supervision, and adherence to operational standards plays a greater role in improving employee performance than other leadership styles. This research is expected to provide considerations in human resource management at Puskesmas.